1979
DOI: 10.1002/mana.19790910105
|View full text |Cite
|
Sign up to set email alerts
|

Über eine topologische Verallgemeinerung von KRULLringen

Abstract: EinleitungEs werden topologische Ringe betrachtet, die Durchschnitte von diskreten Bewertungsringen sind und statt der Endlichkeitsbedingung der Kanwsinge eine topologische Endlichkeitsbedingung erftillen. Die dadurch definierten topologischen Kmmringe (Definition 2) erftillen h n n eine der Endlichkeitsbedingung der Kmmringe entsprechende Abziihlbarkeitsbdmgung (Proposition 1). Zu den topologischen Kmmringen gehoren insbesondere die in naturlicher Weise definierten topologischen ZPE-Ringe (Definition 5). Beis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Many results on the valuation theory of A(X) have also been obtained [1], [2]. In this note we show that a large portion of the results on the rings A(X) extend to the W-rings with complete principal divisor space which were defined by J. Klingen in [15], [16]. Therefore, many properties of A(C) are shared by its non-archimedian counterparts studied by M. Lazard, M. Krasner, and others [8], [17], [18].…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Many results on the valuation theory of A(X) have also been obtained [1], [2]. In this note we show that a large portion of the results on the rings A(X) extend to the W-rings with complete principal divisor space which were defined by J. Klingen in [15], [16]. Therefore, many properties of A(C) are shared by its non-archimedian counterparts studied by M. Lazard, M. Krasner, and others [8], [17], [18].…”
mentioning
confidence: 78%
“…Then by [8,17,18] L k shares many properties of the ring A(C) of entire functions. In [15,Satz 5.2] it was shown that L k is a VV-ring with representation field k and HT(L k ) complete. The following result shows that if k has cardinality 2 N°, then the ideal theory of L k is virtually identical to that of A(X) for any non-compact connected Riemann surface X.…”
Section: Then W(a)aw(b) = W{c)ew(i 1 + I 2 ) So Wu^a W(i 2 )Q W(i^ +mentioning
confidence: 99%
See 1 more Smart Citation